Pemikiran Manajerial Muhammad Al-Fatih Dalam Pembangunan Institusi Pendidikan - Zubeir Ahmad Nasution; Rian Hidayat; Muslim Afandi (Global Action and Education for Society, 2025)
This study aims to examine in depth the managerial thinking of Muhammad Al-Fatih in the development of educational institutions through a library research approach. Muhammad Al-Fatih is known not only as a military and political leader, but also as an Islamic educational figure who has a long-term vision of civilization. This study found that Al-Fatih's managerial thinking rests on three main pillars, namely the pursuit of knowledge as a form of worship and social obligation, character development based on Islamic values such as exemplary, sincerity, and discipline, as well as the spiritual responsibility of education which is not only borne by individuals, but also becomes the duty of the state. In addition, education in Al-Fatih's leadership functioned as a geopolitical instrument, namely as a tool of diplomacy and regeneration of global-minded leaders. These values are represented in the madrasa system, integrative curriculum, and narrative approach in shaping students' characters. The results of the study show that Al-Fatih's thinking is very relevant to the challenges of modern Islamic education, especially in forming an education system that is characterized, competitive, and based on spiritual values. Therefore, Al-Fatih's managerial approach can be used as a strategic model for the development of contemporary Islamic education in Indonesia.